2007
DOI: 10.36487/acg_repo/711_4
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Versus Inelastic Numerical Modelling of Deep and Highly Stressed Mining Fronts

Abstract: With the current trend of exploiting mines at increasing depths comes the challenge of managing increasingly high stress conditions. One tool at the disposal of mine engineers and designers is the numerical simulation of the stresses and deformations likely to be encountered ahead of the mining fronts for various mining scenarios. Although the benefits of numerical modelling are by now well accepted throughout the industry, the applicability of the various types of numerical modelling approaches is not always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The applicability of the linear elastic model, however, is still the subject of much debate by professionals. Andrieux et al (2007) could demonstrate and prove, through worked examples, that in many cases it can be very difficult to correctly interpret the results computed by an elastic approach, particularly when highly stressed mining fronts are involved, and extensive failure occurs. Although some practitioners still trust and prefer the simplistic elastic approaches, it is now widely accepted within the mining community that this approach has a limited range of applicability and, if applied outside its applicable ranges, it can lead to very misleading and potentially dangerous outcomes.…”
Section: Elastic Modelmentioning
confidence: 99%
“…The applicability of the linear elastic model, however, is still the subject of much debate by professionals. Andrieux et al (2007) could demonstrate and prove, through worked examples, that in many cases it can be very difficult to correctly interpret the results computed by an elastic approach, particularly when highly stressed mining fronts are involved, and extensive failure occurs. Although some practitioners still trust and prefer the simplistic elastic approaches, it is now widely accepted within the mining community that this approach has a limited range of applicability and, if applied outside its applicable ranges, it can lead to very misleading and potentially dangerous outcomes.…”
Section: Elastic Modelmentioning
confidence: 99%
“…Furthermore, the capacity to generate stress and deformation results in a reasonable amount of time was important in selecting a numerical package given the number of modelling steps associated with the 14 years of mining covered in this study. In dealing with a three-dimensional space, numerical models based on a linear elastic response of the material, as opposed to more complex non-linear behaviours, result in significantly less computation time (Andrieux et al 2007). Simple or parsimonious models that use the simplest possible concepts and smallest possible number of inputs can have great ranges of explanation in geomechanics (Hammah & Curran 2009).…”
Section: Mining-induced Stressesmentioning
confidence: 99%
“…In some cases, stoping induced stresses (as inputs to the empirical design approaches) are estimated based on linear-elastic numerical models. Andrieux et al (2007) have previously shown how simplified constitutive relationships can provide significant variance in the location of induced stresses within a regional stoping sequence.…”
Section: Stressmentioning
confidence: 99%